Fear Of Use: Electronic Word Of Mouth Effects On Purchase Intention Through Perceived Risk And Attitude Toward Menstrual Cup - Regina Rosita; Heriyadi Heriyadi; Bintoro Bagus Purmono; Juniwati Juniwati; Ahmadi Ahmadi (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Environmental problems, particularly sanitary pad waste in Indonesia, have driven society to develop sustainable solutions. Menstrual cups are an alternative to sanitary pads that can be used over the long term. However, the level of menstrual cup usage in Indonesia remains relatively low compared to other countries. This study aims to analyze the effect of Negative Electronic Word of Mouth on Purchase Intention through Perceived Risk and Attitude Toward Product as mediating variables. This research employs a quantitative method involving 300 respondents who are women in Indonesia and are aware of menstrual cup products. Data were collected through online questionnaires distributed via Google Forms and analyzed using Partial Least Square–Structural Equation Modelling (PLS-SEM) with SmartPLS version 4.0. The results indicate that Negative Electronic Word of Mouth has a negative but insignificant effect on Purchase Intention. On the other hand, Perceived Risk and Attitude Toward Product have a significant effect on Purchase Intention. Furthermore, Perceived Risk and Attitude Toward Product are proven to mediate the relationship between Negative Electronic Word of Mouth and Purchase Intention. These findings emphasize that consumers’ purchase intentions toward a product are not only influenced by information received through social media, but also by consumers’ perceptions and attitudes toward the product.